Mutu Pelayanan Kesehatan Menurut Persepsi Pasien di Puskesmas Tersertifikasi dan Belum Tersertifikasi ISO 9001:2000 di Kota Pekalongan - Yuni Arti (Pena Medika Jurnal Kesehatan, 2010)
ISO 9001:2000 is an indicator of health service in Quality Management System it accommodates basic quality system for providing quality health service  based Standar Operating Procedures. The research purposes knowing patient evaluating of health services accepted in Public Health Center Certificated and non Certificated  ISO 9001:2000. The results of research for promoting health service of public health center. Method used descriptive-analitic with case control design, case is Puskesmas ISO and control is Puskesmas non-ISO. Population are patient whom visit public health center entire Pekalongan City, determining of sample size by quota which number of cases are 40 samples and controls are 40 samples. Data collection by interviewing respondences. Interview did in Puskesmas ISO that Puskesmas Kusuma Bangsa and Puskesmas Jenggot, Puskesmas non-ISO includes Puskesmas Bendan and Puskesmas Kramatsari. Results of data analyzing refer patients appreciate for Puskesmas ISO are regard with Puskesmas non-ISO. Better evaluating of Puskesmas ISO for the number of human resources and drugs quality. Cross tabulation shows patients satisfaction majority in Puskesmas non-ISO, statistic tests result known there isn’t relation betwen ISO 9001:2000 Sertification and patient satisfaction ( p = 0,762). Needed more socialization of ISO 9001:2000 Certification to promote image of public health center by extending health service for wealthy families.Keywords : Health Service, Public Health Center, ISO 9001:2000 Certificatio